Information technology in deciding of technological problems in instrument-making and machine engineering - Antonyuk, V. S.; Vysloukh, S. P. (Видавництво Львівської політехніки, 2013)
Виконано аналіз використання інформаційних технологій під час розв’язання задач технологічної підготовки виробництва в приладо- та машинобудуванні. Показано, що для розв’язання задач стиснення інформаційних масивів, класифікації, групування та розпізнавання образів доцільно використовувати методи багатовимірного статистичного аналізу. Наведено ефективні методи параметричного та структурного моделювання під час розв’язання технологічних задач та рекомендації з їх використання. Вказано на доцільність використання запропонованих методів за інформаційної підтримки життєвого циклу виробів. The analysis of the information technologies usage has been done at manufacturing technological preparation tasks solution in instrument – and machine building. It is showed that for the informative massifs compression tasks solution, classification, grouping and recognition of patterns, it is expedient to use the methods of multidimensional statistical analysis. The effective methods of parametric and structural design at solution of technological tasks and recommendation of their use have been made. It was painted on expedience of the offered methods use at informative support of wares life cycle.